Pre-existing interstitial lung disease as a risk factor for pneumonitis associated with ramucirumab and paclitaxel in patients with gastric cancer: The impact of usual interstitial pneumonia. - Nobuyuki Koyama; Sou Katayanagi; Shigeyuki Kawachi (PLoS ONE)
Objective Combination treatment with ramucirumab and paclitaxel shows significant efficacy in patients with advanced gastric cancer as a second-line standard therapy. However, limited information is available about the development of pneumonitis associated with this treatment in clinical practice. This study aimed to characterize this form of pneumonitis and identify the risk factors for its onset. Methods We retrospectively analyzed the medical records of 44 patients with gastric cancer who received combination treatment with ramucirumab and paclitaxel from 2016 to 2017. Then, the clinicopathological characteristics of patients who developed treatment-related pneumonitis were evaluated and further compared with those of patients who did not. Results Six patients (13.6%) developed pneumonitis within five treatment cycles, and in five cases, remission was observed after cessation of combination treatment alone. The onset of pneumonitis was independently associated with pre-existing interstitial lung disease (ILD) (p = 0.025; odds ratio = 206.4). Patients with pneumonitis showed reduced time to treatment failure (median 56 vs. 138 days; p = 0.008), as compared with those without pneumonitis. Most patients with pre-existing ILD with a usual interstitial pneumonia (UIP) pattern developed pneumonitis. Conclusions In clinical practice, pneumonitis associated with the combination treatment of ramucirumab and paclitaxel was generally mild, but common. Patients with gastric cancer with pre-existing ILD, particularly those presenting with a UIP pattern, undergoing this combination treatment, should be carefully monitored for the development of treatment-related pneumonitis.